Conceptualizing truth : implications for teaching and learning - Krahenbuhl, Kevin S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"It has been widely noted that society has moved away from seeing truth as an objective and, in some ways, important part of what it means to be educated. Varied conceptions of truth have existed and have been debated in the halls of academia for years but recently a shift has occurred in which truth has lost its status broadly as a virtue. In fact, in 2016, Oxford Dictionary declared "post-truth" as its international word of the year, defined as: 'relating to or denoting circumstances in which objective facts are less influential in shaping public opinion than appeals to emotion and personal belief'. Living in a world that is post-truth has direct implications on the education of a society's youth. This book will examine several broad conceptions of truth and present them as truth profiles considering their implications for education. This survey will consider the role of truth as it relates to teaching and the act of being a teacher, engage with challenging questions about what curriculum will be learned and its implications for our understanding of truth and specific consideration is attended to the impacts that one's conception of truth has for what they prioritize in the classroom, their instructional practice, and on learning itself. This book will take a focused look at the concept of truth and how varied conceptions of truth impact teaching and learning through theoretical, analytic, and practical examples"-- Provided by publisher.
Includes index.
Keywords: Education -- Philosophy.; Truth -- Study and teaching.; Learning -- Philosophy.; Education -- Aims & Objectives.; Moral and social purpose of education.; Educational strategies and policy.; elektronické knihy; electronic books